The narrative sentences as the basic model in the context of relations of affirmation / negation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The semantic and communicative structures of narrative sentence in the aspect of affirmation / negation are analysed, its status among other types of sentence is determined. It is found out, that narrative sentences are a base for the study of affirmative or negative meaning.
Keywords: affirmation; denial; narrative sentences; statement; basic model; context; meaning